"There's like no support system": the life course stories of women with children about growing up, becoming mothers, and becoming homeless. Issue 2 (2nd July 2020) - Cronley, Courtney; Nahar, Shamsun; Hohn, Kris
ABSTRACT: The current study reports on a narrative analysis of the stories of women ( N  = 20, 40% African American) with children who have been or are currently homeless with a focus on the women's experiences during childhood, becoming homeless, and becoming mothers, and for some, exiting homelessness. We employed the life course theoretical framework to identify six themes across two developmental periods, pre-adulthood and adulthood: (1) c onstant fragmentation, (2) sudden fragmentation, (3) constrained agency, (4) learned substance abuse, (5) independence aborted, and (6) without a net . All reported childhoods characterized by disruption, although for some this only occurred after a lifechanging family event such as parental divorce or death. The majority described entering abusive relationships as adults and all became pregnant before the age of 20. Lacking family and friends able to help, they found themselves with limited economic options and often self-medicating through substance abuse that had been modeled in childhood and/or reinforced in adulthood. Findings underscore the need for rapid re-housing using a trauma-informed housing first model. Certain events in childhood, specifically parental divorce or death, are critical junctures for homeless prevention services. Further, evidence of reproductive coercion indicates that contraception, family planning, and economic supports may be critical targets for homeless prevention among women, as all of our participants reported an unplanned pregnancy by the age of 20 and poverty, often due to lack of education and job skills, rendering them dependent on male partners and abuse relationships.